RETRACTED: Conceptualizing Post-COVID-19 Malaysia’s Tourism Recovery: An Auto-Regressive Neural Network Analysis - Anantha Raj A. Arokiasamy; Philip Michael Ross Smith; Thanapat Kijbumrung (Emerging Science Journal, 2021)
This article has been retracted: please see Emerging Science Journal policies:(https://ijournalse.org/index.php/ESJ/about/editorialPolicies).Reason: The present article has been retracted at the request of the Research Ethics, Integrity, and Governance team at RMIT University, Australia. Following a research integrity investigation into multiple allegations against former staff member Dr. Alex Arokiasamy, it was found, on the balance of probabilities, that Dr. Arokiasamy breached the Australian Code and/or RMIT Policy by: 1) assigning authorship to individuals who did not make a significant intellectual or scholarly contribution, and 2) publishing a paper with a 40% similarity to other publications.